Interreligious Dialogue in The Qur’an: Interpretations of Al-tabari And Sayyid Qutb - Abdul Mukti, Mohd Fakhrudin (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This paper seeks to discuss Qur’anic perspectives on “People of the Book” (ahl al-kitab) with particular historic reference to the Jews and the Christians. This discussion is based on selected verses of the Qur’an as these have been interpreted by two prominent Muslim commentators of different eras. The two are al-Tabari (838-923), a classical commentator, and Syed Qutb (1903-1966), a modern commentator. Qur’anic teachings on “People of the Book” are important, because these greatly influence and shape inter-faith relations between Muslims and the followers of other religions, particularly the Jews and the Christians. The Qur’an is the main shaper of Muslim attitudes toward the Jews and the Christians in every era in Islamic history. But there are also non-religious factor peculiar to each era-political, cultural, and other – that influence Muslim attitudes toward the Jews and the Christians. That historical factors play a role in determining Muslim attitudes toward the Jews and the Christian is reflected in the commentaries of the two selected scholars. This paper also discusses the factors which may explain the current Muslim lukewarm response to inter-faith dialogue with the Jews and the Christian, especially with the former. It present some of the outstanding obstacles to dialogue, the most important of which pertains to a misinterpretation of the Qur’anic idea of jihad not only among the Jews and the Christians but also among the Muslims. The paper then makes several suggestions on how to improve the state of inter-faith dialogue among the three religious groups.